A System for Monitoring Public Political Groups in WhatsApp - Resende, Gustavo; Messias, Johnnatan; Silva, Márcio; Almeida, Jussara; Vasconcelos, Marisa; Benevenuto, Fabrício (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2018)
In Brazil, 48% of the population use WhatsApp to share and discuss news. Currently, there are serious concerns that this platform can become a fertile ground for groups interested in disseminating misinformation, especially as part of articulated political campaigns. Particularly, WhatsApp provides an important space for users to engage in public conversations that worth attention, the public groups. These groups are suitable for political activism and social movement organization. Additionally, it is reasonable to assume that a malicious misinformation campaign might attempt to maximize the audience of a fake story by sharing it in existing public groups. In this paper, we present a system for gathering, analyzing and visualize public groups in WhatsApp. In addition to describe our methodology, we also provide a brief characterization of the content shared in 127 Brazilian groups. We hope our system can help journalists and researchers to understand the repercussion of events related to the Brazilian elections within these groups.